Mobile Phone Controlling Home Appliances - Ramlee, Ridza Azri; Tang, Daphne Hui Zyen; Othman, Mohd Azlishah; Ismail, Mohd Muzafar; Sulaiman, Hamzah Asyrani; Misran, Mohamad Harris; Meor Said, Maizatul Alice; Abd Aziz, Mohamad Zoinol Abidin (Penerbit Universiti, UTeM, 2013)
Advancement in wireless technology nowadays has allowed the creation of various remote control systems, one of which is the famous Smart Home concept. This project focuses on the development of a smart home system that allows user control of electrical appliances using devices such as laptop or an Android phone via Bluetooth. The system adapts serial connection of the devices with a Bluetooth module and a PIC microcontroller attached on the main circuit board where the microcontroller will then control the home appliances via a relay circuit. The smart home system will be able to ease the effort of physically challenged individuals in controlling their home appliances such as lamps, fan, air-con and etc. Users can trigger the switches anywhere as long as the device is within the vicinity of the Bluetooth signal in the main panel. Moreover, users can also control the appliances via internet connection by sending an email to a specified address. However, this addition requires that the laptop be wirelessly connected to the main board at all times and have internet connection. Generally, the project software application together with its Graphical User Interface was developed using Microsoft© Visual Studio in VB language for the computer platform and Eclipse IDE for the Android platform. The microcontroller, PIC16F877A located on the main circuit board was programmed in C language using MPLAB IDE software and debugged together with the circuit design using Proteus 7 ISIS. The PCB was designed using Proteus 7 ARES. The final prototype of the system was built to demonstrate the proposed functionality of the system.